Gaya Komunikasi Bupati Indragiri Hulu dalam Menjalankan Tugas - Yozani, Ringgo; Situmorang, Jawalter; Firdaus, Muhammad (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
Women's representation to become regional heads has the same position and opportunities as men. At 27 years old, Rezita Meylani Yopi is the youngest and first woman to serve as Regional Head in Indragiri Hulu Regency, Riau Province. At this relatively young age, Rezita's approach to building relationships through communication has its appeal both in government and in society. This research aims to analyze Rezita Meylani Yopi's communication style in carrying out her duties as Regent of Indragiri Hulu. The research method used is a qualitative research method with a descriptive approach. The location of this research was carried out at the Regent's Office of Indragiri Hulu Regency, Riau Province. The results of the research show that the communication style used by Rezita in carrying out her duties as Regent of Indragiri Hulu is an Equality Communication Style. This communication style prioritizes an emotional approach to building relationships with the public in Indragiri Hulu Regency. Apart from that, the communication that was built also depicted two-way communication that was not only centered on Rezita as the regional leader.